Istikhdam Nadzam al-Jazariyah fi Ta'lim al-Lughah al-Arabiyah bi-Madah al-Ashwat li-Tarqiyah Qudrah al-Talamidz 'ala Nutqi al-Huruf al-Hijaiyah fi al-Ma'had al-Islami - Syafei, Isop; Yusup, Maulana (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This research aimed to determine students’ abilities in the Arabic phonology to pronounce hijaiyyah letters before using nazham jazariyyah, to know students’ abilities to pronounce hijaiyyah letters after using nazham jazariyyah, and to know the developmental level of students’ abilities to pronounce hijaiyyah letters after using nazham jazariyyah in the context of middle-class students of Miftahut Taufiq Islamic Boarding School Cibiru Bandung. This study adopted a quasi-experimental method with a pre-test and post-test design. The data collection techniques covered observation, interviews, tests, and literature study.  The research sample subsumed middle-class students at the Miftahut Taufiq Islamic Boarding School, totaling 26 students. this study revealed the following: (1) The middle-class students’ abilities at the Miftahut Taufiq Islamic Boarding School, Cibiru Bandung, to pronounce the hijaiyyah letters before the use of nadzam jazariyyah obtained a value of 39.03. This value showed a low criterion because it was between 30-40 in the value range. (2) The students’ abilities to pronounce hijaiyyah letters after the use of nadzam jazariyyah obtained a score of 71.73. This value showed a high criterion because it was between 70-80 in the value range. (3) The developmental level of students' abilities to pronounce hijaiyyah letters after the use of nadzam jazariyyah according to the n-gain score was 0.63 or 63% at the moderate level.